Thermal convection in rotating anisotropic bidispersive porous layers. (December 2020) - Capone, F; De Luca, R; Gentile, M
Highlights: A mathematical model for fluid dynamics in a rotating bidispersive porous medium, horizontally isotropic, is introduced. Linear and nonlinear stability analyses for thermal convection are performed. The coincidence between linear instability and non-linear stability thresholds has been proved. The influence of a uniform rotation on the onset of convection has been examined. Abstract: Linear and nonlinear stability analyses for thermal convection in a rotating bidispersive porous medium, horizontally isotropic, is performed. Since the coincidence between linear instability and non-linear stability thresholds has been proved, the linear theory captures completely the physics of the problem at stake.